COVID-19 and sustainable environment: understanding higher education students' willingness to pay more for food delivery containers - Sia, Joseph; Hii, Ivy; Ho, Jie Min (EMERALD GROUP PUBLISHING LTD, 2023)
Purpose: The Coronavirus disease 2019 (COVID-19) pandemic has increased the use of food delivery containers in the food and beverage industry. Based on the theory of planned behavior (TPB), the aim of this paper is twofold: Firstly, it examines the influence of three elements of TPB (attitude, perceived behavioral control and subjective norm) and time pressure on the intention to reuse reusable food delivery containers (ITR). Secondly, it examines ITR as an antecedent to the willingness to pay more for reusable food delivery containers (WTPM). Design/methodology/approach: Data were collected from 401 higher education institution (HEI) students and analyzed using partial least squares structural equation modelling (PLS-SEM). Findings: The study found that the three elements of TPB influenced ITR. Furthermore, the results revealed that ITR directly influenced WTPM. Surprisingly, time pressure did not influence ITR. Originality/value: The research is one of the earliest studies to investigate HEI students' intention to reuse food delivery containers during the COVID-19 pandemic. The study contributes to TPB by presenting a novel, integrated model to explain the independent roles of time pressure and ITR on ITR and WTPM, respectively. Finally, it contributes to the existing body of knowledge on pro-environmental behavior among HEI students and advances methodologically by establishing the PLS-SEM approach.